Effects of moringa leaf powder substitution on organoleptic characteristics, iron, and vitamin C of calamansi orange gummy candy - Nabila Salwa; Aripin Ahmad; Eva Fitriyaningsih; Rosi Novita; Syuja’ Rafiqi Arifin; Cut Aja Nuraskin (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2025)
Gummy candy is widely consumed but generally low in micronutrients. Fortification with local ingredients rich in iron and vitamin C may improve its nutritional value. This study aimed to determine the effects of substituting moringa (Moringa oleifera) leaf powder solution on the organoleptic characteristics, iron content, and vitamin C levels of calamansi orange gummy candy. This experimental study employed a Completely Randomized Design and was conducted at the Food Laboratory, Department of Nutrition, Poltekkes Kemenkes Aceh, with chemical analyses performed at BSPJI Banda Aceh from November to December 2024. Three formulations with 30%, 40%, and 50% moringa leaf powder solution were prepared in triplicates. The organoleptic acceptance (color, taste, aroma, and texture) was evaluated using a hedonic test by 30 semi-trained panelists. Iron content was analyzed using atomic absorption spectrophotometry, and vitamin C content was determined by titration. Data were analyzed using analysis of variance (ANOVA), followed by Duncan’s Multiple Range Test (α = 0.05). The results showed that the substitution significantly affected the iron and vitamin C content (p < 0.001). Iron levels increased significantly with higher substitution levels (0.16 ± 0.01, 0.21 ± 0.00, and 0.26 ± 0.02 mg per 25 g; Duncan a < b < c). Vitamin C levels also differed significantly, with the 30% formulation showing higher values than the 40% and 50% formulations (3.31 ± 0.00 mg vs. 3.10 ± 0.01 mg and 3.03 ± 0.00 mg per 25 g, respectively; Duncan a > b = b). In conclusion, substitution with moringa leaf powder solution improves the micronutrient content of calamansi gummy candy, with the 50% formulation providing the highest iron content.